Parental-reported allergic disorders and emergency department presentations for allergy in the first five years of life; a longitudinal birth cohort - Gerben Keijzers; Amy Sweeny; Julia Crilly; Norm Good; Cate M. Cameron; Gabor Mihala; Rani Scott; Paul A. Scuffham (BMC, 2018)
Abstract Background To measure rates of parental-report of allergic disorders and ED presentations for allergic disorders in children, and to describe factors associated with either. Methods An existing cohort of 3404 children born between 2006 and 2011 (Environments for Healthy Living) with prospectively collected pre-natal, perinatal and follow-up data were linked to i) nationwide Medicare and pharmaceutical data and ii) Emergency Department (ED) data from four hospitals in Australia. Parental-reported allergy was assessed in those who returned follow-up questionnaires. ED presentation was defined as any presentation for a suite of allergic disorders, excluding asthma. Univariate analysis and multivariate logistic regression were used to descibe risk factors for both parental-reported allergy and ED presentation for an allergic disorder. Results The incidence of parental-reported child allergy at 1, 3 and 5 years of age was 7.8, 7.8 and 12.6%, respectively. Independent predictors of parental-report of allergy in multivariate analysis were parental-report of asthma (OR 2.2, 95% CI 1.4-3.4) or eczema (OR 4.3, 95% CI 3.1-6.1) and age > 6 months at introduction of solids (OR 1.3, 95% CI 1.0-1.7). Factors associated with ED presentations for allergy, which occurred in 3.6% of the cohort, were presence of maternal asthma (OR 2.3 95% CI:1.1, 4.9) and child born in spring (OR 1.7, 95% CI 1.1, 2.7). Conclusions More than 10% of children up to 5 years have a parental-reported allergic disorder, and 3.6% presented to ED. Parental-report of eczema and/or asthma and late introduction of solids were predictors of parental-report of allergy. Spring birth and maternal asthma were predictors for ED presentation for allergy.